A Catalyst‐Free Cascade Reaction for the Selective Assembly of 3‐Hydroxyisoindolinones on Water. Issue 11 (2nd October 2019) - Li, Pinyi; Jia, Xiuwen; Ma, Xiaoli; Ma, Wenbo; Sheng, Yilin; Zhao, Jingwei; Zhao, Fei
Abstract: A catalyst‐ and additive‐free cascade reaction between 2‐alkynylbenzoic acids and nitrogen‐containing nucleophiles for the selective assembly of 3‐hydroxyisoindolinones on water has been developed. This protocol features readily available starting materials, an environmentally benign solvent, simple operation, extraordinarily broad substrate scope, good functional group tolerance, excellent selectivity, good to excellent yields, high atom‐ and step‐economy, and high bond‐forming efficiency, thus providing a convenient and highly efficient access to 3‐hydroxyisoindolinones. This is an example of 3‐hydroxyisoindolinone synthesis under catalyst‐ and additive‐free conditions, suggesting the synthetic potential of this method. Abstract : Simply extraordinary ! A catalyst‐ and additive‐free cascade reaction between 2‐alkynylbenzoic acids and nitrogen‐containing nucleophiles for the selective assembly of 3‐hydroxyisoindolinones on water is described. This method also shows excellent synthetic potential.